2017
DOI: 10.18632/oncotarget.17599
|View full text |Cite
|
Sign up to set email alerts
|

A nation-wide retrospective epidemiological study of gastroenteropancreatic neuroendocrine neoplasms in china

Abstract: BackgroundRepresentative data on the gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs) in Asian patients is rare, especially in China. This study aims to create a GEP-NENs profile of Chinese patients.MethodsThis was a hospital-based, nation-wide, and multi-center 10-year (2001-2010) retrospective study which collected GEP-NEN patients’ information in tertiary referral hospitals. All 2010 inpatient GEP-NEN cases with confirmed pathology in the selected hospitals were included. The primary GEP-NEN sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
63
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 29 publications
11
63
2
2
Order By: Relevance
“…Our findings are consistent with previous epidemiological data from other Asian series [5-8]. However, some variability exists in the incidence of GEPNEN in these Asian countries.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings are consistent with previous epidemiological data from other Asian series [5-8]. However, some variability exists in the incidence of GEPNEN in these Asian countries.…”
Section: Discussionsupporting
confidence: 92%
“…However, some variability exists in the incidence of GEPNEN in these Asian countries. A nation-wide retrospective epidemiological study of GEPNEN in China (2,010 patients) reported its incidence as 31.5% for the pancreas, 29.6% for the rectum and 27.0% for the stomach [8]. Similarly, a retrospective study from a tertiary medical centre in Hong Kong (126 patients), reported its incidence as 32% (pancreas), 30% (rectum) and 27% (stomach) [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations